Inhibitory Potential of Dietary Nutraceuticals on Cellular PI3K/Akt Signaling: Implications in Cancer Prevention and Therapy - Narayanankutty, Arunaksharan (Current Topics in Medicinal Chemistry, 2021)
Background: The phosphatidyl inositol-3 kinase (PI3K)/protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) signaling has been associated with many cellular physiological events, such as proliferation, maturation, survival, and metabolism. Besides its role in normal cells, the pathway is often upregulated in various cancers. Due to its prominent role in the cancer progression events, it is now being considered as a target for cancer therapy and cancer chemoprevention. Objectives: The present review provides a concise outline of the role of the PI3K/Akt/mTOR pathway in carcinogenesis and progression events, including metastasis, drug resistance and stemness. Further, emphasis needs to be placed on the PI3K/Akt/mTOR pathway inhibitory potentials of various food-derived bioactive components in cancer prevention. Methods: Data on the PI3K/Akt/mTOR inhibiting natural products and their bioactive compounds have been obtained from PubMed/Medline, Scopus, Eurekaselect, etc. Findings from the above citation databases from 2000-2021 are included in the manuscript. Results: Numerous compounds from plants have been isolated and identified as anticancer agents; among these, a predominant class is nutraceuticals. The PI3K pathway is the predominant target of these natural products, and many of these drug candidates are under various stages of drug development. These compounds have shown a significant inhibitory effect on the kinase activities of PI3K and Akt, resulting in the abrogation of cancer initiation and progression events. In addition, these compounds have been shown to reverse the resistance to chemotherapeutic drugs and also reduce the population of cancer stem cells. Conclusion: The nutraceuticals are promising candidates as anticancer agents by blocking PI3K signaling cascades. As the PI3K is a central pathway to various receptors signaling, the dietary intervention may prove to be highly effective.
Keywords: Metastasis